Ablechroiulus spelaeus sp. n. and A. dudichi Andrássy, 1970 from Andalucía Oriental, Spain, with a discussion of the taxonomy of the genus Ablechroiulus Andrássy, 1966 (Nematoda, Rhabditida, Rhabditidae) - Abolafia, Joaquín; Peña-Santiago, Reyes (Zootaxa, 2011)
One new and one known (but uncommon) species of the genus Ablechroiulus are described and illustrated from natural areas in the Iberian Peninsula. Ablechroiulus spelaeus sp. n. is characterized by having body length 0.81–1.48 mm in females and 0.74–1.20 mm in males, lip region nearly continuous and 9–13 μm wide, stoma 23–29 µm long or 1.8–2.7 times the lip region width, neck 166-265 μm long, metacorpus well differentiated, oviduct with a small sac, V = 55–59, female tail (51–60 µm, c = 14–25, c’ = 1.9–2.7) with two marked sections, male tail (52, 58 µm, c = 14.3, 20.7, c’ = 2.0) with filiform posterior part, bursa leptoderan and with nine pairs of papillae (1+2/1+2+1+2), spicules 40, 44 µm long having a terminal protuberance, and gubernaculum 20, 24 µm long. Furthermore, one female of A. dudichi Andrássy, 1970 is described from the north of the Iberian Peninsula. Descriptions, measurements and illustrations are presented for the two species, and SEM pictures are provided for A. spelaeus sp. n. The identity of Ablechroiulus is discussed, including a historical outline, its morphological characterization, and a discussion on the status of several of its species. An emended diagnosis of the genus is provided as well as a list of its species and a key to their identification.